Discovery and characterization of a novel humanized anti-IL-15 antibody and its relevance for the treatment of refractory celiac disease and eosinophilic esophagitis. Issue 6 (18th August 2017) - Vicari, Alain P.; Schoepfer, Alain M.; Meresse, Bertrand; Goffin, Laurence; Léger, Olivier; Josserand, Soheila; Guégan, Nicolas; Yousefi, Shida; Straumann, Alex; Cerf-Bensussan, Nadine; Simon, Hans-Uwe; Chvatchko, Yolande
ABSTRACT: Interleukin-15 (IL-15) is a critical regulator of immune responses, especially at mucosal interfaces within the gastro-intestinal tract. Here, we describe the discovery and characterization of a humanized antibody to IL-15. Data from its epitope and mode of action, cell biology and primate pharmacology, as well as translational studies in human samples and in vivo proof-of-concept experiments in mouse models demonstrate the therapeutic potential of this new antibody targeting IL-15 for refractory celiac disease and eosinophilic esophagitis.